1977
DOI: 10.1111/j.1751-1097.1977.tb07526.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll Metabolism in Etiolated Gherkin Seedlings I. Photoinhibition of Chlorophyll Accumulation

Abstract: Abstract. Cotyledons of etiolated gherkin seedlings do not turn green upon transfer to high intensity red light (about 25 W/m2). A pre‐irradiation with high intensity red light has an after‐effect as chlorophyll accumulation during a subsequent exposure to white light (20 W/m2) is inhibited. The capacity of protochlorophyll regeneration during a dark period depends on the length of a previous light period but is hardly affected by the light intensity. At high intensity light the rate of protochlorophyll regen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1985
1985

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Pf~ has a stabilizing action on Chl in light [35] and Chl might thus be protected from photobleaching. It was repeatedly observed that under higher irradiances Chl is lost due to photobleaching [28,34,14,45] ; R especially favours photodestruction of Chl [15] as well as decreasing the capacity of P Chl Ode) biosynthesis at later stages of development [42]. Photobleaching might be involved under high R during the first hours of irradiations (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Pf~ has a stabilizing action on Chl in light [35] and Chl might thus be protected from photobleaching. It was repeatedly observed that under higher irradiances Chl is lost due to photobleaching [28,34,14,45] ; R especially favours photodestruction of Chl [15] as well as decreasing the capacity of P Chl Ode) biosynthesis at later stages of development [42]. Photobleaching might be involved under high R during the first hours of irradiations (Fig.…”
Section: Discussionmentioning
confidence: 99%